Investigation of Rapid Rewarming Chips for Cryopreservation by Joule Heating - Han, Hengxin (Langmuir : the ACS journal of surfaces and colloids, 2023)
Rapid and uniform rewarming is critical to cryopreservation. Current rapid rewarming methods require complex physical field application devices (such as lasers or radio frequencies) and the addition of nanoparticles as heating media. These complex devices and nanoparticles limit the promotion of the rapid rewarming method and pose potential biosafety concerns. In this work, a joule heating-based rapid electric heating chip (EHC) was designed for cryopreservation. Uniform and rapid rewarming of biological samples in different volumes can be achieved through simple operations. EHC loaded with 0.28 mL of CPA solution can achieve a rewarming rate of 3.2 × 105 °C/min (2.8 mL with 2.3 × 103 °C/min), approximately 2 orders of magnitude greater than the rewarming rates observed with an equal capacity straw when combined with laser nanowarming or magnetic induction heating. In addition, the degree of supercooling can be significantly reduced without manual nucleation during the cooling of the EHC. Subsequently, the results of cryopreservation validation of cells and spheroids showed that the cell viability and spheroid structural integrity were significantly improved after cryopreservation. The viability of human lung adenocarcinoma (A549) cells postcryopreservation was 97.2%, which was significantly higher than 93% in the cryogenic vials (CV) group. Similar results were seen in human mesenchymal stem cells (MSCs), with 93.18% cell survival in the EHC group, significantly higher than 86.83% in the CV group, and cells in the EHC group were also significantly better than those in the CV group for further apoptosis and necrosis assays. This work provides an efficient rewarming protocol for the cryopreservation of biological samples, significantly improving the quantity and quality of cells and spheroids postcryopreservation